SECS Analysis of Nighttime Magnetic Perturbation Events Observed in Arctic Canada. Issue 11 (2nd November 2021) - Weygand, James M.; Engebretson, Mark J.; Pilipenko, Viacheslav A.; Steinmetz, Erik S.; Moldwin, Mark B.; Connors, Martin G.; Nishimura, Yukitoshi; Lyons, Larry R.; Russell, Christopher T.; Ohtani, Shin‐Ichi; Gjerloev, Jesper
Abstract: Large changes of the magnetic field associated with magnetic perturbation events (MPEs) with amplitudes |Δ B | of hundreds of nT and 5–10 min duration have been frequently observed within a few hours of midnight. This study compares the statistical location of nighttime MPEs with |d B /d t | ≥ 6 nT/s within the auroral current system observed during 2015 and 2017 at two stations, Cape Dorset and Kuujjuarapik, in Eastern Canada. Maps of the two dimensional nightside auroral current system were derived using the Spherical Elementary Current Systems (SECS) technique. Analyses were produced at each station for all events, and for premidnight and postmidnight subsets. We examine four MPE intervals in detail, two accompanied by auroral images, and show the varying associations between MPEs and overhead ionospheric current systems including electrojets and the field‐aligned like currents. We find 225 of 279 MPEs occurred within the westward electrojet and only 3 within the eastward electrojet. For the premidnight MPEs 100 of 230 events occurred within the Harang current system while many of the remainder occurred within either the downward region 1 current system or the upward region 2 current system. Many of the 49 postmidnight MPEs occurred in either the downward region 1 (11 events) or upward region 2 current system (27 events). These result suggest that the source of MPEs in the premidnight sector is somewhere between the inner to mid plasma sheet and the source for the MPEs in the postmidnight sector is somewhere between the inner magnetosphere and the inner plasma sheet. Key Points: Magnetic perturbation events most frequently occur within a westward electrojet Premidnight MPEs commonly occur within the Harang current system and Postmidnight MPEs commonly occur within the region 2 upward currents Magnetic perturbation events with all sky image data display a sudden brightening and distortion of auroral arcs